First in Man Pilot Feasibility Study in Extracranial Carotid Robotic-Assisted Endovascular Intervention. Issue 3 (11th December 2020) - Desai, Virendra R; Lee, Jonathan J; Sample, Trevis; Kleiman, Neal S; Lumsden, Alan; Britz, Gavin W
Abstract: BACKGROUND: Robotic-assistance in endovascular intervention represents a nascent yet promising innovation. OBJECTIVE: To present the first human experience utilizing robotic-assisted angiography in the extracranial carotid circulation. METHODS: Between March 2019 and September 2019, patients with extracranial carotid circulation pathology presenting to Houston Methodist Hospital were enrolled. RESULTS: A total of 6 patients met inclusion criteria: 5 underwent diagnostic angiography only with robotic-assisted catheter manipulation, while 1 underwent both diagnostic followed by delayed therapeutic intervention. Mean age was 51 +/− 17.5 yr. Mean anesthesia time was 158.7 +/− 37.9 min, mean fluoroscopic time was 22.0 +/− 7.3 min, and mean radiation dose was 815.0 +/− 517.0 mGy. There were no technical complications and no clinical deficits postprocedure. None of the cases required conversion to manual neurovascular intervention (NVI). CONCLUSION: Incorporating robotic technology in NVI can enhance procedural technique and diminish occupational hazards. Its application in the coronary and peripheral vascular settings has established safety and efficacy, but in the neurovascular setting, this has yet to be demonstrated. This study presents the first in human feasibility experience of robotic-assisted NVI in the extracranial carotid circulation.